A Hermeneutical Study of Using Mobile Phone in 4.0 in Writing Skills - Dewi Zulaiha; Yunika Triana (ELE Reviews: English Language Education Reviews, 2021)
Mobile phones become an affordable device in our lives since it is ubiquitous and the function is now not only for communication but also beyond that. This study aims to give the readers more insight into the use of a mobile phone in writing skills by using a hermeneutical approach. Participants were undergraduate students at age 18-20 (N=16). The descriptive analysis results reveal that a significant number of students notice that writing is considered the most challenging skill since they have to organize all aspects to produce good writing. Thus, a hermeneutical approach is needed to examine their difficulties in writing skills.